SOME ASPECTS ABOUT MATERIAL RECYCLING - Florin CIOFU (Fiabilitate şi Durabilitate, 2023)
In the various process industries, the choice of materials is a very important step that is made according to many criteria. Part of these selection criteria relates to material properties - mechanical, electrical, thermal, corrosion and so on; the performance of a particular component depends on the properties of the material from which it is made. The processability or ease of manufacture of the component may also play a role in the selection process. In engineering practice, other important criteria must be considered in the development of a marketable product. Some of these involve environmental and social issues such as pollution, disposal, recycling, toxicity and energy. This paper, in one way or another, addresses these issues related to material properties and manufacturing, as well as a relatively brief presentation of environmental and social considerations that are important in engineering practice.